Summer temperatures during the last glaciation (MIS 5c to MIS 3) inferred from a 50,000-year chironomid record from Furamoos, southern Germany - Bolland, Alexander; Kern, Oliver A.; Allstädt, Frederik J.; Peteet, Dorothy; Koutsodendris, Andreas; Pross, Jörg; Heiri, Oliver (Quaternary science reviews, 2021)
There is a sparsity of long, continuous palaeotemperature records for the last glacial period in central Europe, particularly for the interval corresponding to Marine Isotope Stages (MIS) 4 and 3. Here we present a new, ca. 50-thousand year (ka)-long chironomid record from Furamoos, southern Germany, covering the interval from MIS 5a to MIS 3 that we use to examine lake development and then to quantitatively reconstruct mean July air temperatures. Chironomid assemblages with high abundances of taxa such as Polypedilum nubeculosum-type, Microtendipes pedellus-type, Cladopelma lateralis-type and Dicrotendipes nervosus-type imply a shallow-lake setting for the majority of the examined interval, which is corroborated by other aquatic remains such as oribatid mites, Sialidae and Ceratopogonidae. Assemblages from the interval ca. 99 to 80 ka (in the region corresponding to the Brorup Interstadial, Stadial B and early Odderade Interstadial) are dominated by taxa such as Tanytarsus glabrescens-type and Tanytarsus mendax-type and indicate relatively warm temperatures. Assemblages from the interval covering ca. 80 to 54 ka (corresponding to the late Odderade, Stadial C, Durnten Interstadial and Stadial D) are dominated by taxa such as Sergentia coracina-type and Tanytarsus lugens-type and are typical for cooler conditions. Reconstructed July temperatures for the early Wurmian (Brorup to early Odderade; ca. 99-80 ka) are 13-14 degrees C. Values decline to <10 degrees C during the late Odderade and Stadial C (ca. 80-77 ka) around the MIS 5a/4 transition. This decrease is coeval with a pronounced decrease in Northern Hemisphere summer insolation. Values stay in the range of 9-11 degrees C during the Durnten and Stadial D (ca. 54-74.5 ka) and increase again to 12.5 degrees C during the Bellamont 1 interstadial (ca. 54-46 ka). Reconstructed July temperatures track changes in arboreal pollen percentages at Furamoos and agree with a summer-temperature decrease during the early to mid-Wurmian as reported by other palaeotemperature records from Europe and the North Atlantic. Our chironomid record from Furamoos provides valuable new insights into Wurmian climate dynamics in Central Europe, and corroborates other temperature reconstructions from the early to mid-Wurmian glacial period. (C) 2021 The Authors. Published by Elsevier Ltd.